Reading Interest and Reading Comprehension Ability: The Correlational Study in Secondary Education - Kurniati, Risti; Daud, Afrianto; Masyhur, Masyhur (Journal of Education, Language Innovation, and Applied Linguistics, 2023)
This study aimed to determine whether there is a positive correlation between reading interest and reading comprehension ability of the eleventh-grade students of SMAN 10 Pekanbaru. This study used a quantitative method to obtain data from participants. Using random sampling, the writers took 31 students from class XI MIPA 7 at SMAN 10 Pekanbaru. The data were collected using a questionnaire and reading test. Based on the results of the data analysis, the writer found that the correlation value between the two variables is 0.423, which means that there is a positive correlation between reading interest and students' reading comprehension. In addition, because the value of correlation is 0.423, it can be interpreted that this correlation is at the level of moderate correlation. Furthermore, the value of Sig. (2-tailed) is 0.018, meaning that the value of Sig. (2-tailed) is smaller than 0.05. Based on this, it can be concluded that (Ha) was accepted and (Ho) was rejected. This finding suggests that there is a positive correlation between reading interest and students’ reading comprehension. Keywords: Reading Interest, Reading Comprehension, Correlation.